AB0397 PREDICTION OF RECURRENCE AFTER DISCONTINUATION OF ADALIMUMAB BY USING ULTRASOUND ASSESSMENT -THE PROUD STUDY-. (June 2019) - Okano, Tadashi; Hara, Ryota; Wada, Makoto; Koike, Tatsuya; Mamoto, Kenji; Sugioka, Yuko; Tada, Masahiro; Fujimura, Takanori; Sendo, Sho; Okano, Takaichi; Ichise, Yoshihide; Naka, Ikuko; et al.
Abstract : Background: Tapering of biological disease-modifying anti-rheumatic drugs (DMARDs) is recommended by European League Against Rheumatism (EULAR) in patients with stable rheumatoid arthritis (RA) disease activity. Discontinuation of biological DMARDs can be successful in some patients. However, the predictive factors enabling established patients with RA to remain free of biological DMARDs is unclear. Recently, ultrasonography (US) has become an important imaging tool to identify subclinical synovitis, even in patients with remission. There have been few reports on whether residual synovitis as shown by US can predict relapse of disease activity after discontinuation of biological DMARDs. Objectives: We aimed to investigate the usefulness of US for predicting relapse in patients in remission for RA after discontinuation of adalimumab (ADA). Methods: Patients who were using ADA and in remission (Disease Activity Score 28-joint count C reactive protein (DAS28-CRP) <2.6) for longer than 24 weeks were included in this multicenter prospective study. ADA was stopped and patients were followed up until week 52. Predictive factors for relapse at 24 and 52 weeks were analyzed from baseline clinical data, including a US examination. ADA was restarted at the time of relapse (DAS28-CRP ≥3.2). US assessment was performed at 0, 12, 24, 36, and 52 weeks and at the time of relapse. A US examination was performed at the bilateral first to fifth metacarpophalangeal joints, first interphalangeal and second to fifth proximal interphalangeal joints, and first to fifth metatarsophalangeal joints, by using a high-frequency linear transducer. The gray scale (GS) and power Doppler (PD) signals were scored in each synovial site using a semi-quantitative scale from 0 to 3. Moreover, the modified Total Sharp Score (mTSS) was evaluated at 0, 24, and 52 weeks by conventional radiography. The patients who relapsed were administrated ADA again. Results: Fifty-three patients were included. Ten (18.9%) patients relapsed up to week 24 and 20 (37.7%) patients relapsed up to 52 weeks. The relapsed patients tended to have a long disease duration, but baseline US findings could not predict relapse. Increases in the PD score were observed during follow-up in some relapsed patients. Disease activity control was good after ADA was restarted in the relapsed group, and there was no difference in progression of the mTSS in the relapsed and non-relapsed groups. Conclusion: Predicting relapse by baseline US findings after discontinuation of ADA in remission is difficult. However, an increased PD score in a following US examination might be useful for early detection of relapse. Radiographic progression is not significantly different in patients with relapse and those without relapse. References: [1] Iwamoto T, Ikeda K, Hosokawa J, et al. Prediction of relapse after discontinuation of biologic agents by ultrasonographic assessment in patients with rheumatoid arthritis in clinical remission: high predictive values of total gray-scale and power Doppler scores that represent residual synovial inflammation before discontinuation. Arthritis Care Res (Hoboken). 2014;66:1576-81. Disclosure of Interests: Tadashi Okano Speakers bureau: AbbVie, Ryota Hara: None declared, Makoto Wada: None declared, Tatsuya Koike Speakers bureau: AbbVie, Astellas Pharma Inc., Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen, Lilly, Mitsubishi Tanabe Pharma Corporation, MSD, Ono Pharmaceutical, Pfizer, Roche, Takeda Pharmaceutical, Teijin Pharma, and UCB, Kenji Mamoto: None declared, Yuko Sugioka: None declared, Masahiro Tada Speakers bureau: Abbvie, Astellas Pharma, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma Corporation, Ono Pharmaceutical, Pfizer Japan, Takeda Pharmaceutical, Takanori Fujimura: None declared, Sho Sendo: None declared, Takaichi Okano: None declared, Yoshihide Ichise: None declared, Ikuko Naka: None declared, Heiseki Yu: None declared, Akihiko Nakabayashi: None declared, Yoshinobu Matsuura: None declared, Takahiro Yoshikawa: None declared, Masao Tamura: None declared, Masayasu Kitano: None declared, Yasuhide Kanayama: None declared